(untitled) (Journal of Comparative & International Higher Education, 2024)
Higher education internationalization has become an increasingly challenging endeavor. The outbreak of the COVID-19 virus and the ever-changing landscape of immigration policies have called for a need to reexamine how universities internationalize. Transnational virtual classrooms or virtual exchanges have been shown to provide students with a more equal opportunity to develop their global competencies and cultural skills than study abroad. Traditional internationalization methods may no longer be as effective as they have been in the past, creating a need to reconceptualize how we educate college students for global competencies. This research in-progress summarizes a portion of a dissertation. The aim of this qualitative study is to investigate global citizenship student awareness in a virtual exchange. This study presents preliminary findings of their experiences; applied global citizenship and virtual exchange as a channel.